2021
DOI: 10.3390/foods10010180
|View full text |Cite
|
Sign up to set email alerts
|

Combined Extract of Leonurus japonicus Houtt, Eclipta prostrata L., and Pueraria lobata Ohwi Improved Hot Flashes and Depression in an Ovariectomized Rat Model of Menopause

Abstract: Menopause leads to ovarian hormone loss, which causes symptoms such as weight gain, hot flashes, and depression. Exploring nutraceuticals is important for treating menopausal symptoms that extensively impact women’s quality of life. We hypothesized that a combination of Leonurus japonicus Houtt, Eclipta prostrata L., and Pueraria lobata Ohwi (LEPE) would alleviate menopausal symptoms in an ovariectomized menopausal rat model. Bilateral ovariectomy was performed and animals were assigned to five groups: (1) Sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…It was reported that the ethanol extract of Puerariae Radix can significantly shorten the fixed time of the forced swimming test (FST) and tail suspension test (TST) with cerebral ischemia-reperfusion and reverse the norepinephrine (NE) and 4-dihydroxyphenylacetic acid-induced ptcerebral ischemia-reperfusion of protein in the hippocampus and striatum of mice [ 14 ]. It has been demonstrated that Pueraria lobata Ohwi could ameliorate depression-related behavior, including in FST and TST that are influencing depression in an ovariectomized rat menopause model [ 15 ]. It was revealed that the combination of Puerariae Radix and hawthorn fruit could prevent depression in a diabetic rat model [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the ethanol extract of Puerariae Radix can significantly shorten the fixed time of the forced swimming test (FST) and tail suspension test (TST) with cerebral ischemia-reperfusion and reverse the norepinephrine (NE) and 4-dihydroxyphenylacetic acid-induced ptcerebral ischemia-reperfusion of protein in the hippocampus and striatum of mice [ 14 ]. It has been demonstrated that Pueraria lobata Ohwi could ameliorate depression-related behavior, including in FST and TST that are influencing depression in an ovariectomized rat menopause model [ 15 ]. It was revealed that the combination of Puerariae Radix and hawthorn fruit could prevent depression in a diabetic rat model [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with depression often have intractable sleep disorders, with an incidence of up to 98%, which are manifested in insomnia, difficulty falling asleep, early awakening, sleep rhythm disorder, poor sleep quality with long course of disease, and high recurrence rate [20]. Previous studies have been demonstrated that Puerariae Radix and its extracts have powerful antidepressant effects in recent years [14][15][16][17][18][19]. However, because of the complex composition of Puerariae Radix, its main material basis and molecular mechanism for the treatment of depression are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the wide range of ethnomedicinal values and applications, several studies have been performed regarding the biological activities of extracts and compounds obtained from E. prostrata using both in vitro and in vivo models [ 59 , 60 , 61 ]. Some of them are discussed in detail in following sub-sections.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…The aerial part of Leonurus japonicus Houtt., also called Yimucao, has the traditional effects of activation of blood circulation, regulation of menstruation, diuresis, detumescence, clearance of heat and detoxification, and is often used to treat irregular menstruation, dysmenorrhea, lochia and postpartum hemorrhage (Miao et al, 2019). The pharmacological activities of Yimucao, such as lipid‐lowering, anti‐inflammatory, anti‐allergic, immunomodulatory, anti‐tumor, anti‐depressant, cardioprotective and angiogenesis promotion, jointly reveal the mechanism of its traditional efficacy (Chen et al, 2017; Kang et al, 2021; Lee et al, 2017; Liao et al, 2021; Yue et al, 2020; Zhang et al, 2021; Zhang, Zhong, et al, 2020). The compatibility of Danggui and Yimucao can be traced back to the classic traditional Chinese medicine prescription “Yimu Wan”.…”
Section: Introductionmentioning
confidence: 99%